Narrative Text Development: Analysis On Students’ Writing Difficulties - Muhammad Ali Sukran; Taufiq Kurniawan (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2022)
The English language is being used more and more often, which pushes nations and individuals to thoroughly learn it. Although there have been several attempts to increase awareness of English use, many students still object to the language being used in an academic setting. Because English writing is the most challenging talent, students and teachers who concentrate on it reach a saturation point. However, given that one of the issues is that learners have a hard time writing in English, it is important to identify the underlying causes of these issues. Consequently, the bases' answers are modified to better meet the demands of the learners. This study examined the issues that students have when planning and composing narrative texts. Descriptive and qualitative research methods are used. The research's findings gathered through observation, testing, and interviews. The third semester Hamzanwadi University student was the study's target audience. The findings indicated that difficulties in producing narrative text in terms of syntax, vocabulary, spelling, difficulty, and resolution. There were other contributing elements to the issues, such as how little English is read and written by learners. The students have a variety of options for honing their narrative text writing, including reading books and writing exercises.